More than the heart: Hepatic, renal, and cardiac dysfunction in adult Fontan patients. (7th July 2019) - Byrne, Ryan D.; Weingarten, Angela J.; Clark, Daniel E.; Huang, Shi; Perri, Roman E.; Scanga, Andrew E.; Menachem, Jonathan N.; Markham, Larry W.; Frischhertz, Benjamin P.
Abstract: Setting: Fontan‐associated liver disease universally affects adults with single ventricle heart disease. Chronic kidney disease is also highly prevalent in adult Fontan patients. In this study, we evaluate the relationship of Fontan hemodynamics invasively and noninvasively with extra‐cardiac dysfunction as measured by MELD and MELD‐XI. Objective: We hypothesize that invasive and noninvasive measures of Fontan circuit congestion and ventricular dysfunction are associated with increased MELD and MELD‐XI scores. Design: Single‐center data from adults with Fontan palliation who had ongoing care, including cardiac catheterization, were retrospectively collected. Hemodynamic data from cardiac catheterization and echocardiographic assessment of ventricular and atrioventricular valve function were tested for association with serum creatinine, MELD, and MELD‐XI. Linear regression was used to perform multivariable analysis in the echocardiogram cohort. Results: Fifty‐seven patients had congruent lab and catheterization data for analysis. Sixty‐three and sixty‐nine patients had congruent lab and echocardiogram data for MELD and MELD‐XI, respectively. Of the hemodynamic variables analyzed, only decreased systemic oxygen saturation had significant correlation with elevated MELD and MELD‐XI ( P  = .045). Patients with moderately or severely reduced ejection fraction by echocardiogram had significantly higher MELD and MELD‐XI scores compared to those with normal or mildly depressed systolic ventricular function ( P  = .008 and P  < .001 for MELD and MELD‐XI, respectively). Significant differences in creatinine were also found among the ventricular dysfunction groups ( P  = .02). Conclusions: In adults following Fontan palliation, systolic ventricular dysfunction and decreased oxygen saturation were associated with hepatic and renal dysfunction as assessed by elevated serum creatinine, MELD, and MELD‐XI scores.